Moderating readers and reading online. (August 2016) - Thomas, Bronwen; Round, Julia
Despite the proliferation of online forums for the discussion of literary texts, very little has been written to date on the management of these spaces and how this helps frame the kinds of discussion and interpretative work that take place. This article draws on a series of interviews with moderators of online book-related sites, alongside close analysis of online interactions between moderators and users to consider issues of authority, hierarchy, power and control, asking how these act to structure or facilitate acts of interpretation taking place online. We begin by outlining the moderator's role before conducting a brief review of existing scholarship on offline reading groups and online communities, to identify how social infrastructures are established and negotiated. The main body of the article draws upon interviews with moderators of two online literary forums – The Republic of Pemberley and The Guardian 's online Reading Group – to explore the ways in which each of the respective moderators frames his or her role. This is accompanied by an in-depth exploration of how the forms of interpretation we find on the two sites are shaped and directed by the moderators. The article concludes by reflecting upon some of the issues raised by this study and its methodology, particularly with regards to digital dualism and the blurring of the boundaries between the public and the private in online spaces.